Morphological variability of the Carex oederi s. l. inflorescence - Więcław, Helena (Biodiversity: Research and Conservation, 2011)
The most variable features describing Carex oederi s. l. include: (i) the distance between two lower female spikes, (ii) the length of the peduncle of a lower female spike, (iii) the distance between two upper female spikes, (iv) the length of inflorescence and peduncle of a male spike. Most of observed stems had (3)4-5 female spikes, which were crowded around a sessile and short male spike. Specimens with fewer female spikes (2-3) were characterized generally by their loose positioning on a stem (occasionally a lower female spike was distant and had a peduncle) and the presence of usually longer male spikes on a peduncle. In conclusion, C. oederi s. l. is highly variable morphologically. In the investigated materials, there are no apparent discontinuities. Further (planned) biometric research will be extended to the characteristics of the perygynium and vegetative features.